Credit and Sustainability of SMEs in Uganda: A Case of SMEs in Nakawa Division Kampala - Muhire, Francis; Olyanga, Anthony (Journal of Economics, Finance and Accounting Studies, 2022)
The study was carried out to establish the relationship between Credit terms, Credit accessibility, and Sustainability of Small and Medium Enterprises in Uganda. The objectives guided the study to examine: the sustainability of SMEs, the level of credit accessibility by SMEs, the credit terms by financial institutions, and the combined impact of credit terms and credit accessibility on the sustainability of SMEs in the Nakawa Division. The study was based on a cross-sectional research design and quantitative research approach of 743 registered SMEs in the Nakawa Division and a sample of 248 SMEs. Primary data was collected using questionnaires. Data from the field was compiled, sorted, and edited for analysis using SPSS. The results indicated significant positive relationships between credit terms and sustainability, credit accessibility and sustainability, and credit terms and credit accessibility of SMEs within the Nakawa Division. Based on the findings, the study recommended that financial Institutions need to relax credit terms which will increase credit accessibility which also automatically lead to sustainability; SMEs should ensure mechanisms that can boost their credit accessibility, and the government should put in place policies that ensure easy access to credit by SMEs and should further increase funding and come up with more entrepreneurship oriented programs such as capital ventures which well maximized guarantee sustainability of SMEs.